General Anesthesia versus Sedation, Both with Hemodynamic Control, during Intraarterial Treatment for Stroke: The GASS Randomized Trial. (28th February 2022) - Maurice, Axelle; Eugène, François; Ronzière, Thomas; Devys, Jean-Michel; Taylor, Guillaume; Subileau, Aurélie; Huet, Olivier; Gherbi, Hakim; Laffon, Marc; Esvan, Maxime; Laviolle, Bruno; Beloeil, Helene; et al.
Abstract : Background: It is speculated that the anesthetic strategy during endovascular therapy for stroke may have an impact on the outcome of the patients. The authors hypothesized that conscious sedation is associated with a better functional outcome 3 months after endovascular therapy for the treatment of stroke compared with general anesthesia. Methods: In this single-blind, randomized trial, patients received either a standardized general anesthesia or a standardized conscious sedation. Blood pressure control was also standardized in both groups. The primary outcome measure was a modified Rankin score less than or equal to 2 (0 = no symptoms; 5 = severe disability) assessed 3 months after treatment. The main secondary outcomes were complications, mortality, reperfusion results, and National Institutes of Health Stroke Scores at days 1 and 7. Results: Of 351 randomized patients, 345 were included in the analysis. The primary outcome occurred in 129 of 341 (38%) of the patients: 63 (36%) in the conscious sedation group and 66 (40%) in the general anesthesia group (relative risk, 0.91 [95% CI, 0.69 to 1.19]; P = 0.474). Patients in the general anesthesia group experienced more intraoperative hypo- or hypertensive episodes, while the cumulative duration was not different (mean ± SD, 36 ± 31 vs. 39 ± 25 min; P = 0.079). The time from onset and from arrival to puncture were longer in the general anesthesia group (mean difference, 19 min [ i.e., −00:19] [95% CI, −0:38 to 0] and mean difference, 9 min [95% CI, −0:18 to −0:01], respectively), while the time from onset to recanalization was similar in both groups. Recanalization was more often successful in the general anesthesia group (144 of 169 [85%] vs. 131 of 174 [75%]; P = 0.021). The incidence of symptomatic intracranial hemorrhage was similar in both groups. Conclusions: The functional outcomes 3 months after endovascular treatment for stroke were similar with general anesthesia and sedation. Our results, therefore, suggest that clinicians can use either approach. Abstract : In this single-blind, randomized trial including patients with large vessel occlusion of the anterior cerebral circulation, standardized general anesthesia and standardized conscious sedation for endovascular therapy resulted in comparable modified Rankin scores when evaluated 3 months after intervention. These observations suggest that the functional outcome 3 months after endovascular treatment for ischemic stroke is comparable for general anesthesia and sedation.